PENGARUH PASTISIPASI MANAJEMEN DAN KEPUASAN PENGGUNA TERHADAP EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI DI LPD KECAMATAN UBUD - Ni Made Kansa Dewi Putri; Ni Luh Putri Srinadi (UNHI Press, 2020)
The purpose of this study was to analyze the effect of management participation and user satisfaction on the effectiveness of using accounting information systems. This research was conducted in the LPD Sub-district of Ubud, using the observation method, interview method, the literature method, the documentation method, and the survey method by distributing questionnaires to LPD employees in the Sub-district of Ubud, with a population of 263 employees. Determination of the sample using non-probability sampling method with purposive sampling method. The research sample consisted of 87 employees. Data analysis uses Multiple Linear Regression. The results showed that management participation and user satisfaction had a positive and significant effect on the effectiveness of the use of accounting information systems in LPD in Ubud Gianyar, which means that the higher the management participation, the more effective the use of accounting information systems, vice versa and the higher the ability of satisfaction users will increase the effectiveness of using accounting information systems, and vice versa.